Caracterização das propriedades estruturais, reológicas e termoanalíticas do amido da semente de abacate (Persea americana, Mill) modificado por via oxidativa - Bauab, Tábata (2013)
The avocado (Persea americana, Miller) is a tree that is native to North America (Mexico) and it is very popular world wide due to its food applications. Its seeds contain an important amount of starch and there is lack of study and understanding regarding the physico-chemical properties of this biopolymer. In this research, starch granules were extracted from avocado seeds and oxidised with standard sodium hy pochlorite solutions at 0.5, 1.0 and 2.0 %. Untreated and modified samples were investigated using the following techniques: simultaneous thermogravimetry– differential thermal analysis, differential scanning calorimetry, non-contact atomic force microscopy, rapid viscoamylographic analysis and X-ray powder patterns diffractometry. The main purpose was to investigate the thermal, structural and rheological behaviour of native and oxidised avocado starch, and it was verified that the treated samples showed a decrease in gelatinisation enthalpy and average roughness as well as in the degree of relative crystallinity and pasting properties.